Month-of-birth-effect in multiple sclerosis in Austria. (December 2019) - Walleczek, Nina-Katharina; Frommlet, Florian; Bsteh, Gabriel; Eggers, Christian; Rauschka, Helmut; Koppi, Stefan; Assar, Hamid; Ehling, Rainer; Birkl, Christoph; Salhofer-Polanyi, Sabine; Baumgartner, Anna; Blechinger, Stephan; et al.
Background: The month-of-birth-effect (MoBE) describes the finding that multiple sclerosis (MS) patients seem to have been born significantly more frequently in spring, with a rise in May, and significantly less often in autumn and winter with the fewest births in November. Objectives: To analyse if the MoBE can also be found in the Austrian MS population, and if so, whether the pattern is similar to the reported pattern in Canada, United Kingdom, and some Scandinavian countries. Methods: The data of 7886 MS patients in Austria were compared to all live births in Austria from 1940 to 2010, that is, 7.256545 data entries of the Austrian birth registry and analysed in detail. Results: Patterns observed in our MS cohort were not different from patterns in the general population, even when stratifying for gender. However, the noticeable and partly significant ups and downs over the examined years did not follow the distinct specific pattern with highest birth rates in spring and lowest birth rates in autumn that has been described previously for countries above the 49th latitude. Conclusion: After correcting for month-of-birth patterns in the general Austrian population, there is no evidence for the previously described MoBE in Austrian MS patients.